IPERMOB: Infrastruttura Pervasiva Eterogenea Real-time per il controllo della Mobilità - Mambrini, Raffaella (GEOmedia, 2010)
IPERMOB proposes an information system for monitoring and management of urban mobility, using innovative and open technologies. From the architectural point of view, the system has three levels (tiers) that separate the issues relating to the collection and aggregation of data from those relating to publication of the information and use of services.